PRACTICAL APPLICATION OF CARBON DIOXIDE FOR THE EXTRACTION OF VARIOUS MEDICINAL AND AROMATIC SEEDS - Venskutonis, P. R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Medicinal and aromatic seeds were extracted with liquid carbon dioxide (L-CO2) in order to measure extract yields, the content and composition of essential oils, which are the most important characteristics for the assessment of technological and economical feasibility of commercial applications of the extraction techniques. Preliminary assessment of some biological activities of the extracts, such as radical scavenging capacity and inhibition of microorganisms were also tested. Pilot plant scale extractions were performed using seeds from 9 species: coriander (Coriandrum sativum), caraway (Carum carvi), dill (Anethum graveolens), fennel (Foeniculum vulgare), blue fenugreek (Trigonella coerulea), sicklefruit fenugreek (Trigonella foenum-graecum), amaranth (Amaranthus lividus retroflexus), black cumin (Nigella sativa) and white mustard (Sinapis alba). Different extraction cycles were applied to increase the yield of the extract. Depending on the process time, particle size and extraction cycle the yields varied from 2.3 (sicklefruit fenugreek) to 18 % (black cumin), while the content of the essential oil in extracts was from the traces to 27.5 %. The highest yields were obtained from the seeds containing remarkable amounts of essential oil and lipids. Essential oil composition was analyzed by using gas chromatography and mass spectrometry and the differences between hydrodistilled oils from the whole ground seeds and their extracts were evaluated. It was concluded extraction of some plant seeds with L-CO2 is economically and technologically feasible process for commercial applications, e.g. producing ingredients for the formulations of different products, particularly flavorings, functional foods and food supplements.